Bibliometric analysis of publications on concrete with waste reuse from the Web of Science database (Research, Society and Development, 2020)
The growing demand for alternative materials to replace natural aggregates has made it possible to reuse construction waste for the production of concrete. This increase in the search for alternative materials was only possible, in addition to other factors, due to the increase in publications indexed within this theme. The objective of this research was to carry out a bibliometric survey of publications on concrete with reuse of residues, allowing quantitative and qualitative analysis on the evolution of publications, the main journals and events in the area, the most relevant authors and institutions and the studied residues. The work addresses aspects of publications related to the topic of reuse of waste in concrete, using bibliometric tools that allowed analyzing Brazilian publications on the subject. The bibliometric survey was carried out from 1998 to 2017 in the Web of Science database and made it possible to verify the most productive authors and institutions, the most studied residues, cooperation networks between authors and countries, in addition to the most influential journals and events and significant on the topic. The study revealed growing interest in this topic, with emphasis on construction and demolition waste. Although civil construction is the subject of many works, Brazilian publications on concrete with reuse of residues are still incipient, there were gaps in publications, such as the low degree of collaboration between authors in the area, especially at the international level, with authors from Asia. and Africa, in addition to the low frequency of publication of works that use waste in the production of special concretes.